Craft Beverages and Tourism, Volume 2 Environmental, Societal, and Marketing Implications (Springer International Publishing, 2018)
This volume applies a mix of qualitative and quantitative research and case studies to analyze the role that the craft beverage industry plays within society at large. It targets important themes such as environmental conservation and social responsibility, as well as the psychology of the craft beer drinker and their impact on tourism marketing. This volume advances marketing, hospitality, and leisure studies research for academics, industry experts, and emerging entrepreneurs. .